Bio-fertilizers in Organic Agriculture - Samoon3, H. A. Rather4, Showkat A. Dar5; B. Zehra6, S. Sheraz Mahdi1*, G. I. Hassan2, S. A. (Journal of Phytology, 2010)
Experiencing the adverse effects of synthetic input dependent agriculture the concept of organic agriculture is gaining momentum. Almost 31 million hectares of land are currently managed organically by more than 6, 00, 000 farmers worldwide, constitutes 0.7 per cent of agriculture land. India had brought more than 2.5 m ha land under certification of organics. In these systems production is based in synergism with nature, which makes systems of unending life i.e. sustainable. Deteriorative effects of synthetic chemical inputs are obvious, but, at the same time we need to revive soil health and living which support to sustainable production system. Soil environment needs to be made congenial for living of useful microbial population, responsible for continuous availability of nutrients from natural sources. Bio-fertilizers being essential components of organic farming play vital role in maintaining long term soil fertility and sustainability by fixing atmospheric dinitrogen (N=N), mobilizing fixed macro and micro nutrients or convert insoluble P in the soil into forms available to plants, there by increases their efficiency and availability. Currently there is a gap of ten million tonnes of plant nutrients between removal of crops and supply through chemical fertilizers. In context of both the cost and environmental impact of chemical fertilizers, excessive reliance on the chemical fertilizers is not viable strategy in long run because of the cost, both in domestic resources and foreign exchange, involved in setting up of fertilizer plants and sustaining the production. In this context, organic manures (bio-fertilizers) would be the viable option for farmers to increase productivity per unit area. Â The mycorrhizal associations (VAM) in alleviating Al toxicity, increasing N, P and micronutrient uptake, maintaining soil structure by the production specific protein called â€œGlomulinâ€ has been repeatedly demonstrated. Liquid bio-fertilizer technology now, shares more advantage over conventional carrier based bio-fertilizers and can be considered as a breakthrough in field of Bio-fertilizer technology and should find greater acceptance by farmers, extension workers and commercial bio-fertilizer manufactures. In this review, the established facts observed and the work carried out by many researchers on bio-fertilizers is discussed. Key words: Bio-fertilizers, Crop growth, Sustainability, VA-mycorrhizae <span style="line-height: 110%; font-variant: normal !important; font-family: ";Book Antiqua";,";serif";; letter-spacing: -0.3pt; font-size: 7pt; font-weight: normal; mso-font-kerning: 0pt; mso-no-proof: no; mso-fareast-language: EN-SG; mso-ansi-language: EN-SG;" lang="EN-SG">S. Sheraz Mahdi et al. Bio-fertilizers in Organic Agriculture. J Phytol 2/10 (2010) 42-54